Naphthyl-functionalized acetamide derivatives: Promising agents for cholinesterase inhibition and antioxidant therapy in Alzheimer's disease (2024)
This study presents the synthesis and characterization of a series of 13 novel acetamides. These were subjected to Ellman's assay to determine the efficacy of the AChE and BChE inhibitors. Finally, we report their antioxidant activity as an alternative approach for the search for drugs to treat AD. These studies revealed that compounds 1a–1k and 2l–2m were obtained in moderate yield. Four amides (1h, 1j, 1k, and 2l) were selective for one of the enzymes (BChE); thus, those that inhibited BChE were more active than the positive control (galantamine) and showed better IC50 values (3.30–5.03 µM). The theoretical free binding energies calculated by MM-GBSA indicated that all inhibitors were more stable than rivastigmine, and the inhibition mechanisms involved the entire active site: peripheral anionic site, oxyanion hole, acyl-binding pockets, and catalytic site. We examined the cytotoxicity of compounds 1h, 1j, 1k, and 2l in human dermal cells and found that they did not exhibit any toxic effects under the tested conditions. Additionally, these compounds, which also inhibited BChE, displayed mixed inhibition and did not exhibit hemolytic effects on human erythrocytes. Furthermore, the ABTS and DPPH assays indicated that, although none of the compounds showed activity in the DPPH assay, the EC50 values for radical trapping by the ABTS method showed that compounds 1a, 1d, 1e, and 1g had EC50 values lower than 10 µg/mL, indicating their strong radical scavenging capacity. We also report the crystal structures of compounds 1c, 1d, 1f, and 1g, which are found in monoclinic crystal systems.